An Analysis of Elastic Scattering Angular Distributions of 17F on a 208Pb Target at Different Energies - Celik, Sule Karatepe; Boztosun, Ismail; Dogru, Mahmut (Springer Wien, 2021)
This study investigated the elastic scattering of a F-17+Pb-208 system at different energies using the Continuum-Discretized Coupled Channels (CDCC) method. A microscopic optical model was selected and double-folding potential was used for the O-16+target interaction. The real part of the optical model was determined as folding potential and the imaginary part of the optical model was taken as standard volume Woods-Saxon shape. Single-channel and multi-channel CDCC calculations were performed to determine the effect of excited channels. An elastic scattering cross section of the F-17+Pb-208 system was calculated and its compatibility with experimental data was determined.